Pengaruh Etika Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Tower Bersama Grup Jakarta - Sanggrama Arya Kencana, Bramamukti; Warpindyastuti, Lady Diana (Universitas 17 Agustus 1945 Semarang, 2024)
Bramamukti (64200807). Work ethics and work environment are important components that can affect employee performance in completing their work. This study aims to determine the effect of work ethics and work environment on employee performance of PT Tower Bersama. This research uses quantitative methods by distributing questionnaires to PT Tower Bersama and the sampling technique in this study uses non-probability sampling method, namely saturated sample technique with a sample size of 62 respondents of PT Tower Bersama employees and sampling techniques using questionnaires and will be tested by the SPSS version 25 application. The data collected is supported by validity test and reliability test to see the feasibility of the data used. Analysis of the research instrument model is supported by classical assumption testing as a condition of multiple linear regression testing, namely: normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test and by testing the coefficient of determination. The results showed that work ethics and work environment have a positive and significant effect partially and simultaneously on the performance of employees of PT Tower Bersama.